Wearable Devices the Big Wave of Innovation - Nasiri, Noushin (IntechOpen, 2019)
Wearable technologies are equipped with microchips and sensors capable of tracking and wirelessly communicating information in real time. With innovations on the horizon, the future of wearable devices will go beyond answering calls or counting our steps to providing us with sophisticated wearable gadgets capable of addressing fundamental and technological challenges. This book investigates the development of wearable technologies across a range of applications from educational assessment to health, biomedical sensing, and energy harvesting. Furthermore, it discusses some key innovations in micro/nano fabrication of these technologies, their basic working mechanisms, and the challenges facing their progress.